Carlo Cecchi: funambolo della scena italiana L'apprendistato e il magistero - SCHEPIS, CHIARA (Premio Ricerca «Città di Firenze», 2017)
Carlo Cecchi: funambolo della scena italiana (Carlo Cecchi: a funambulist of the Italian stage) constitutes the only monograph on the Florentine actor, director and master of dramatic art of the Italian theatre. The book reconstructs the actor's artistic story in order to carve out two attitudes characterizing his relationship with the stage: the personal training path and the modalities of the trainer job: Apprenticeship and magisterium. While this study unwinds, Florence takes on a particular centrality: from an abandoned and renegade homeland to an intentionally rediscovered island, in which the actor-director lives one of the most significant phases of his maturity, directing the Teatro Niccolini from 1980 to 1995 - recently reopened as a school for a wide group of students, actors-protagonists of today's stages.